Analysis of the Effect of Cash Management on Profit Performance with Liquidity as a Moderating Variable in Pharmacy Companies in Indonesia - Rizkha Arum Cantika; Imron Rosyadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates how cash management influences profit performance in Indonesian pharmacy companies, with liquidity positioned as a moderating factor. Using a quantitative approach rooted in the positivist paradigm, the research analyzes secondary data obtained from audited financial statements of pharmacy firms listed on the Indonesia Stock Exchange for the 2021–2024 period. Cash Turnover, Return on Assets (ROA), and the Current Ratio (CR) were used as key indicators to represent cash management, profit performance, and liquidity. Multiple linear regression and Moderated Regression Analysis (MRA) were applied after meeting classical assumption requirements, including tests for normality, multicollinearity, heteroskedasticity, and autocorrelation. The empirical findings indicate that cash management significantly and negatively affects profit performance, suggesting that overly rapid cash turnover may reflect insufficient cash reserves and can weaken profitability. Liquidity shows a positive and significant effect on profit performance, demonstrating its role in supporting operational stability. Additionally, liquidity moderates the relationship between cash management and profit performance by reducing the strength of this influence. These results highlight the importance of balanced cash management and optimal liquidity conditions in ensuring financial sustainability within pharmacy companies. The study also recommends expanding future research through additional variables, broader samples, and alternative analytical frameworks.